2022
DOI: 10.1186/s12903-022-02148-8
|View full text |Cite|
|
Sign up to set email alerts
|

Antibacterial efficacy of peracetic acid in comparison with sodium hypochlorite or chlorhexidine against Enterococcus faecalis and Parvimonas micra

Abstract: Background The main goal of an endodontic treatment is a complete debridement of the root canal system; however, currently mechanical shaping and chemical cleaning procedures for this purpose have deemed non-satisfactory. Methods The efficacy of peracetic acid (PAA; 0.5, 1.0, 2.0%), as a root canal irrigation solution, against Enterococcus faecalis (DSM 20478) and Parvimonas micra (DSM 20468) when compared with the one of sodium hypochlorite (NaOC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…The most significant antimicrobial effects are achieved when using gutta-percha with chlorhexidine, indicating the greatest reduction in bacterial cultures after contact with this substance. Study results indicated that chlorhexidine is effective against Enterococcus faecalis, a notion supported by numerous other studies demonstrating both the in vitro and in vivo effectiveness of this aspect [40][41][42][43][44][45][46][47]. Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…The most significant antimicrobial effects are achieved when using gutta-percha with chlorhexidine, indicating the greatest reduction in bacterial cultures after contact with this substance. Study results indicated that chlorhexidine is effective against Enterococcus faecalis, a notion supported by numerous other studies demonstrating both the in vitro and in vivo effectiveness of this aspect [40][41][42][43][44][45][46][47]. Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…Briseño-Marroquín et al, (2022) [71], observed that PAA (0.5-2.0%) exerted large inhibition zones against E. faecalis and relatively small zones against Parvimonas micra. With This analysis reveals that the antimicrobial effects of some antibiotics are similar.…”
Section: Antibacterial Effect Of Biocidesmentioning
confidence: 98%
“…Briseño-Marroquín et al, (2022) [71], observed that PAA (0.5-2.0%) exerted large inhibition zones against E. faecalis and relatively small zones against Parvimonas micra. With decreasing concentration of 5.0, 3.0, and 1.0% of NaOCl, the diameters of the inhibition zones against E. faecalis also increased.…”
Section: Antibacterial Effect Of Biocidesmentioning
confidence: 98%
“…There are research studies in the literature evaluating the effect of different irrigation protocols on the E.faecalis bio lms (16,23). However, there is limited knowledge regarding the effect of concentrations of the irrigation solutions on their antimicrobial capacity (24). In addition, there is no consensus about the in uence of interactions between the irrigants on eliminating bio lms from the root canal system.…”
Section: Introductionmentioning
confidence: 99%